Development of a premix based on micellar casein for fortification of meat systems with vitamin A - N. A. Dzhangiryan; V. I. Shipulin; D. N. Volodin (Теория и практика переработки мяса, 2024)
A novel approach to the protection of unstable fat-soluble vitamins, using retinol as an example, is presented in this work. This method is based on introducing vitamin A molecules into casein micelles. Protective properties of micellar casein towards different forms of retinol (native vitamin and palmitic acid ester) in vitro and in emulsion-type meat products are investigated. A technology of the introduction using micellar casein concentrate (MCC) has been developed. Conditions similar to those in which vitamin molecules can be in meat emulsions during heat treatment are simulated in vitro. The optimal time of “encapsulation” (2 hours) and the need for additional surfactant (tween-80) are identified. The use of the casein micelles protection made it possible to increase the number of retinol molecules that did not undergo decomposition under model conditions (in vitro) from ~30% to ~80%. Using the vitamin premix the degree of degradation of vitamin molecules does not exceed 4% after heat treatment. Data received allowed us to determine the efficiency of the protection properties of casein micelles for unstable vitamin A molecules.